2010
DOI: 10.1111/j.1365-3040.2010.02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct signalling pathways and transcriptome response signatures differentiate ammonium- and nitrate-supplied plants

Abstract: Nitrogen is the only macronutrient that is commonly available to plants in both oxidized and reduced forms, mainly nitrate and ammonium. The physiological and molecular effects of nitrate supply have been well studied, but comparatively little is known about ammonium nutrition and its differential effects on cell function and gene expression. We have used a physiologically realistic hydroponic growth system to compare the transcriptomes and redox status of the roots of ammonium-and nitrate-supplied Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
233
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(252 citation statements)
references
References 82 publications
(177 reference statements)
18
233
0
1
Order By: Relevance
“…In our experiments NH 4 Cl supply caused a significant increase in amino acids content as compared with KNO 3 and NH 4 NO 3 plants which is consistent with the results of Pasqualini et al (2001);Patterson et al (2010) who proposed that NH 4 + ion diverted the assimilated carbon mainly towards amino acids. As KNO 3 and NH 4 NO 3 nitrogen source resulted in higher nitrogen content, which can be correlated with higher activities of nitrogen metabolizing as well as aminotransferases enzymes as also reported by Below et al (2000).…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments NH 4 Cl supply caused a significant increase in amino acids content as compared with KNO 3 and NH 4 NO 3 plants which is consistent with the results of Pasqualini et al (2001);Patterson et al (2010) who proposed that NH 4 + ion diverted the assimilated carbon mainly towards amino acids. As KNO 3 and NH 4 NO 3 nitrogen source resulted in higher nitrogen content, which can be correlated with higher activities of nitrogen metabolizing as well as aminotransferases enzymes as also reported by Below et al (2000).…”
Section: Discussionsupporting
confidence: 92%
“…In the yeasts Saccharomyces cerevisiae and Candida albicans, the kinase NPR1 regulates ammonium transport (Boeckstaens et al, 2007;Neuhäuser et al, 2011), but the kinase that regulates plant AMT1s is currently unclear. Plant kinases related to S. cerevisiae NPR1 are members of the CIPK family, and some CIPK genes in plants are upregulated during the ammonium response (Canales et al, 2014;Patterson et al, 2010;Engelsberger and Schulze, 2012). However, whether CIPKs are involved in ammonium transport in plants is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, a series of transcriptome analyses have demonstrated that N nutrient regulated expressions of global genes involved in diverse aspects including metabolic and developmental processes (Gutierrez et al, 2008;Patterson et al, 2010;Scheible et al, 2004;Wang et al, 2000). In rice, AMT1;1 and AMT1;2 are up-regulated in response to NH 4 + , whereas AMT1;3 is up-regulated by nitrogen deprivation (Kumar et al, 2003;Sonoda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%